Evaluation of choroidal thickness in patients with obstructive sleep apnea/hypopnea syndrome - Kara,Selcuk (2014)
Purpose: To compare the subfoveal choroidal thickness (SFCT) of patients with different severities of obstructive sleep apnea/hypopnea syndrome (OSAHS) and normal controls via enhanced depth imaging optical coherence tomography (EDI-OCT). Methods: In this retrospective, case-control study, 49 eyes from 49 patients that had undergone polysomnography were included. SFCT of the horizontal and vertical line scans were manually measured for all eyes based on EDI-OCT images. Two separate analyses were performed according to different apnea/hypopnea index (AHI) groupings. Initial testing was conducted using non-OSAHS, mild OSAHS (5≤AHI<15), moderate OSAHS (15≤AHI<30), and severe OSAHS (AHI≥30) patient groupings, while secondary testing used non-OSAHS, mild OSAHS (5≤AHI<15), and moderate/severe OSAHS (AHI≥15) patient groupings. Results: The mean SFCT was 314.5 μm in the non-OSAHS patients (n=14), 324.5 μm in the mild OSAHS patients (n=15), 269.3 μm in the moderate OSAHS patients (n=11), and 264.3 μm in the severe OSAHS patients (n=9). SFCT between the four groups revealed no significant differences despite a trend towards slight thinning in the severe group (P=0.08). When the moderate and severe groups were merged and compared with the mild OASHS and non-OSAHS groups, SFCT of the moderate/severe group was found to be significantly thinner than that of the mild group (P=0.016). A negative significant correlation was found between SFCT and AHI in OSAHS patients (r=0.368, P=0.033). Conclusions: In patients with moderate/severe OSAHS, EDI-OCT revealed a thinned SFCT. Other accompanying systemic or ocular diseases may induce perfusion and oxygenation deficiency in eyes of OSAHS patients. Further studies are required in order to determine the exact relationships between ocular pathologies and clinical grades of OSAHS.